Dental and Oral Health Education for Elemetary School Students through Patient Hygiene Performance Index Indicator - Septian Emma Dwi Jatmika; Muchsin Maulana (Institute of Advanced Engineering and Science, 2018)
Caries is a problem that often occurs in school-age children. Special Region of Yogyakarta is a province that has a high DMF-T index by 5.9 and exceeds the national DMF-T index. One of the efforts to improve dental and oral health of school-age children is the health education method using simulation methods, as well as simple techniques that may attract children's attention and be understood. The aim of the current study is to knowing the influence of oral and dental hygiene education intervention on dental and oral hygiene level at SD Negeri 3 Sleman students. This research used a kind of quasi experimental research with one group pretest posttest design. The research was done in SD Negeri 3 Sleman, the sample used was the 3rd graders from 57 students in 2017. The intervention was done by dental and oral hygiene education. Respondents were examined related to their dental and oral hygiene levels. It was measured by the PHP Index (Patient Hygiene Perfomance) before and after the intervention. According to results, The average score of respondents’dental and oral hygine pre test was 0.0823 and the average post test score of respondents’dental and oral hygiene was 1.4830. There is the difference of 1.4007. This shows an increament in oral hygiene of the respondent before and after the education. The results of statistical analysis show that there is an influence of oral and dental hygiene which pvalue 0,000 <0.05. Thus, there is a need for dental and mouth hygiene education to be conducted regularly and delivered with an interesting method.